2015
DOI: 10.1155/2015/636891
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum 25-Hydroxy Vitamin D and Insulin Sensitivity and  β-Cell Function in Newly Diagnosed Type 2 Diabetes

Abstract: The aim of this study was to investigate the relationship between serum 25-hydroxy vitamin D (25-OHD) and insulin sensitivity and β-cell function in newly diagnosed type 2 diabetes. 395 newly diagnosed type 2 diabetes patients were enrolled in this study. Venous blood samples were collected at 0 min, 30 min, and 120 min of OGTT to measure serum glucose and insulin. Matsuda ISI and HOMA-IR were used to determine insulin sensitivity. The ratio of 0–120 min area under curve of insulin to glucose (insulin release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…In studies on the association between vitamin D and beta cell function, previous results were not consistent according to ethnicity and country, healthy subjects and subjects with disease. ( 16 20 , 30 32 ) Kayaniyil and his colleagues ( 16 ) evaluated the association between 25(OH)D and beta cell dysfunction in type 2 diabetes and suggested that the serum 25(OH)D level was positively associated with beta cell function ( p <0.001). On the other hand, some studies reported that the association of serum 25(OH)D level and HOMA- B is not relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on the association between vitamin D and beta cell function, previous results were not consistent according to ethnicity and country, healthy subjects and subjects with disease. ( 16 20 , 30 32 ) Kayaniyil and his colleagues ( 16 ) evaluated the association between 25(OH)D and beta cell dysfunction in type 2 diabetes and suggested that the serum 25(OH)D level was positively associated with beta cell function ( p <0.001). On the other hand, some studies reported that the association of serum 25(OH)D level and HOMA- B is not relevant.…”
Section: Discussionmentioning
confidence: 99%
“… Diabetic subject studies for the lower BMI quartile (<30): Forest plot shows the correlation between vitamin D status and BMI [ 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. A random effect model was used to calculate the correlations and 95% CI ( I 2 = 54.584%, p = 0.00).…”
Section: Figurementioning
confidence: 99%
“… Authors’ assessment of the risk of bias in the diabetic subject studies: Data shown for each individual study (the plus sign shows a low risk of bias, the minus sign shows a high risk of bias, and the question mark indicates that the risk of bias is unknown) [ 22 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. …”
Section: Figurementioning
confidence: 99%
“…Few studies have focused on the sex disparity in the relationship between vitamin D and insulin sensitivity and b-cell dysfunction up to now. Gao et al has reported that the vitamin D level is significantly associated with female b-cell function, whereas in the male population, these associations are null (38). For the Western population, vitamin D deficiency was found to be associated with decreased insulin production in males with T2DM (9).…”
Section: Discussionmentioning
confidence: 99%